2013
DOI: 10.1016/j.jviromet.2013.07.006
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a Rift Valley fever real-time RT-PCR assay that can detect all three genome segments

Abstract: Outbreaks of Rift Valley fever in Kenya, Madagascar, Mauritania, and South Africa had devastating effects on livestock and human health. In addition, this disease is a food security issue for endemic countries. There is growing concern for the potential introduction of RVF into non-endemic countries. A number of single-gene target amplification assays have been developed for the rapid detection of RVF viral RNA. This paper describes the development of an improved amplification assay that includes two confirmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…Blood samples were centrifuged and sera were kept at −80°C and shipped to La Reunion (France) for laboratory testing. To look for acute infections, detection of RVF virus genome was performed using the RT-PCR technique based on the L segment with a detection limit of 0.5 TCID 50 /mL (Wilson et al 2013). Evidence of past infections was examined by detecting RVF-specific IgG antibodies in serum (ID Screen RVF Competition multispecies ELISA kit; IDVet, Grabels, France) with a diagnostic sensitivity of 98% and specificity of 100% (Kortekaas et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were centrifuged and sera were kept at −80°C and shipped to La Reunion (France) for laboratory testing. To look for acute infections, detection of RVF virus genome was performed using the RT-PCR technique based on the L segment with a detection limit of 0.5 TCID 50 /mL (Wilson et al 2013). Evidence of past infections was examined by detecting RVF-specific IgG antibodies in serum (ID Screen RVF Competition multispecies ELISA kit; IDVet, Grabels, France) with a diagnostic sensitivity of 98% and specificity of 100% (Kortekaas et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…This assay was successfully validated on human RVF clinical samples, and has clinical diagnostic capabilities out to at least 10 days post-symptomonset. The assay developed by Wilson et al amplifies the L and M segments as confirmatory targets, and includes a third target gene, NSs, which is deleted in multiple vaccine candidates (64). This approach will be tremendously advantageous for simultaneously monitoring vaccine coverage vs. virus spread.…”
Section: Molecular Detection Qrt-pcrmentioning
confidence: 99%
“…As there is no ideal vaccine, developing a rapid detection and diagnosis technology has important agricultural and public health significance for RVFV control in both epidemic and non-epidemic areas [14]. Presently, apart from traditional methods such as virus isolation, serology diagnosis, virus neutralization testing, and hemagglutination inhibition tests, there are also RT-PCR [15], ELISA [2], nested RT-PCR [16], fluorescence RT-PCR [3], and RT-LAMP [17] technologies available for detecting and diagnosing RVFV. As there is no RVFV pathogen in China, because of the pathogen's characteristics (such as being harmful to both human and animals, and its high transmissibility, pathogenicity, and perniciousness), research on RVFV is seldom reported in China [18].…”
Section: Sensitivity and Specificity Of Rvfv Rt-lampmentioning
confidence: 99%
“…When infected by RVFV, pregnant dams show an abortion rate of 90 -100 %. The mortality rate for adult animals of different species varies in the range 10 to 60 %, and that of newborn lambs reaches 90 -100 % [2][3][4]. Humans infected by the virus have moderate symptoms such as chills, headache, and pain in the extremities (that is, influenza-like symptoms) or there may be other unapparent symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation